Refuge?
Refuge?, shot by WITNESS partner Rencontre Africaine pour la Defense des Droits de l'Homme (RADDHO), with music and narration by Philip Hamilton, documents the social and economic conditions of Mauritanian, Liberian and Sierra Leonean refugees in Senegal. This video was screened at a briefing during the 2000 ExCom meeting of the UNHCR.